Natural Products as Potential Anti-Alzheimer Agents - Panda, Siva S.; Jhanji, Nancy (Current Medicinal Chemistry, 2020)
Medicinal plants have curative properties due to the presence of various complex chemical substances of different composition, which are found as secondary metabolites in one or more parts of the plant. The diverse secondary metabolites play an important role in the prevention and cure of various diseases including neurodegenerative diseases like Alzheimer’s disease. Naturally occurring compounds such as flavonoids, polyphenols, alkaloids, and glycosides found in various parts of the plant and/or marine sources may potentially protect neurodegeneration as well as improve memory and cognitive function. Many natural compounds show anti-Alzheimer activity through specific pharmacological mechanisms like targeting β-amyloid, Beta-secretase 1 and Acetylcholinesterase. In this review, we have compiled more than 130 natural products with a broad diversity in the class of compounds, which were isolated from different sources showing anti- Alzheimer properties.
Keywords: natural product